ANALISIS PERILAKU HIDUP BERSIH DAN SEHAT DENGAN KEJADIAN COVID-19 TAHUN 2022-20223 DI RUMAH SAKIT UMUM PUSAT H. ADAM MALIK - Harahap, Mery Silvia; ., Irwandi; Rusli, Kevin; Hasian, Muhammad Tsawaby; Rachmasari, Novita; Sembiring, Rasman Gunadi; Sitorus, Friska Ernita; Rosa, Amelia (Deli Medical and Health Science Journal, 2024)
Clean and healthy living behavior (PHBS) is a software established to improve health. for the reason that Covid-19 pandemic, the PHBS program, in particular hand washing with soap, has all started to be socialized on a large scale. therefore, analyzing the fundamental relationship between Covid-19 and one's behavior in dwelling easy and wholesome is crucial. This look at aimed to investigate clean and wholesome living behavior with the preval__ence of Covid-19 in 2022-2023 at H. Adam Malik valuable preferred medical institution.The kind of research used in this observe is quantitative with a Case-manage studies design. The sample on this observe have been patients who had and had never been wonderful for Covid-19 and have been treated at the H. Adam Malik principal trendy health facility in the range of 2022 - 2023, namely eighty human beings. records collection on this observe using a questionnaire. records have been analyzed quantitatively with univariate and bivariate eval__uation. most respondents in this have a look at were aged 26-35 years, male and woman respondents had the equal range, and the general public of respondents in this observe labored as non-medical examiners. The results confirmed that there has been a dating among the use of a mask, washing arms with soap, the use of a hand sanitizer, keeping distance, keeping off crowds, converting garments and bathing when you get home after traveling, consuming nutritious food, and physical pastime for at the least 30 minutes an afternoon, getting sufficient relaxation, masking your mouth when coughing, sneezing, along with your higher arm or tissue and then immediately throwing the tissue right into a closed trash can and straight away washing your fingers (ethics when sneezing and coughing) with the occurrence of Covid-19 with a p-price <zero.05.it is recommended to everybody, in particular health workers in hospitals, to continually practice easy and wholesome living behaviors (PHBS) in normal life, not handiest all through the Covid-19 pandemic.